Effect of Group Based Synchronization on User Anonymity in Mix Networks - Aksoy, Alperen; Kesdogan, Dogan (ACM International Conference Proceeding Series, 2023)
In so-called closed environments, the MIX network can theoretically provide perfect security, i.e. if perfect protection is envisaged, all senders and receivers should be perfectly synchronized and participate equally in each communication round of the MIX technique. In the context of open environments (e.g., the Internet), there is no synchronization between the participants and here the technique is vulnerable to known analyses such as (statistical) disclosure attacks. In short, the Mix technology is highly dependent on its application context in which it involves the participants. In this work, we study the effect of context in terms of synchronization rate, present two different synchronization approaches and evaluate their protection against disclosure attacks.
CRIS-Team Scopus Importer:2023-09-15
Keywords: anonymity; disclosure attacks.; mix-networks; traffic analysis